Gene Profiling of Human Induced Pluripotent Stem Cell-Derived Astrocyte Progenitors Following Spinal Cord Engraftment. (6th March 2014) - Haidet-Phillips, Amanda M.; Roybon, Laurent; Gross, Sarah K.; Tuteja, Alisha; Donnelly, Christopher J.; Richard, Jean-Philippe; Ko, Myungsung; Sherman, Alex; Eggan, Kevin; Henderson, Christopher E.; Maragakis, Nicholas J.
Abstract : This study investigated whether human induced pluripotent stem cell (hiPSC)-derived astrocyte progenitors could be engrafted to the rodent spinal cord and how the characteristics of these cells changed. Results show that human embryonic stem cell- and hiPSC-derived astrocyte progenitors survive long-term after spinal cord engraftment and differentiate to astrocytes in vivo with few cells from other lineages present. Abstract: The generation of human induced pluripotent stem cells (hiPSCs) represents an exciting advancement with promise for stem cell transplantation therapies as well as for neurological disease modeling. Based on the emerging roles for astrocytes in neurological disorders, we investigated whether hiPSC-derived astrocyte progenitors could be engrafted to the rodent spinal cord and how the characteristics of these cells changed between in vitro culture and after transplantation to the in vivo spinal cord environment. Our results show that human embryonic stem cell- and hiPSC-derived astrocyte progenitors survive long-term after spinal cord engraftment and differentiate to astrocytes in vivo with few cells from other lineages present. Gene profiling of the transplanted cells demonstrates the astrocyte progenitors continue to mature in vivo and upregulate a variety of astrocyte-specific genes. Given this mature astrocyte gene profile, this work highlights hiPSCs as a tool to investigate disease-related astrocyte biology using in vivo disease modeling with significant implications for human neurological diseases currently lacking animal models.